Oleic and Linoleic Acids Induce the Release of Neutrophil Extracellular Traps via Pannexin 1-Dependent ATP Release and P2X1 Receptor Activation - Alarcón, Pablo; Manosalva, Carolina; Quiroga, John; Belmar, Isidora; Álvarez, Karina; Díaz, Gustavo; Taubert, Anja; Hermosilla, Carlos; Carretta, María D.; Burgos, Rafael A.; Hidalgo, María A. (Frontiers in Veterinary Science, 2020)
Non-esterified fatty acids (NEFAs) such as oleic acid (OA) and linoleic acid (LA) are associated with a higher incidence of infectious diseases such as metritis and mastitis during the bovine peripartum. Fatty acids can induce an increase in the release of ATP, and changes in the expression levels of purinergic receptors in bovine PMNs during peripartum have also been reported. PMNs respond to inflammatory processes with production of ROS, release of proteolytic and bactericidal proteins, and formation of neutrophil extracellular traps (NETs). NETs formation is known to require ATP production through glycolysis. Studies have shown that the above-mentioned metabolic changes alter innate immune responses, particularly in PMNs. We hypothesized that NEFAs induce the formation of NETs through ATP release by Pannexin 1 and activation of purinergic receptors. In this study, we found that OA and LA induce NET formation and extracellular ATP release. Carbenoxolone, a pannexin-1 (PANX1) inhibitor, reduced OA and LA-induced ATP release. We also found that P2X1, P2X4, P2X5, P2X7, and PANX1 were expressed at the mRNA level in bovine PMNs. Additionally, NEFA-induced NET formation was completely abolished with exposure to NF449, a P2X1 antagonist, and partially inhibited by treatment with etomoxir, an inhibitor of fatty acid oxidation (FAO). Our results suggest that OA and LA induce NET formation and ATP release via PANX1 and activation of P2X1. These new data contribute to explain effects of NEFA high concentrations during the transition period of dairy cattle and further understanding of pro-inflammatory effects and the outcome of postpartum diseases.